2008
DOI: 10.1111/j.1365-294x.2008.03840.x
|View full text |Cite
|
Sign up to set email alerts
|

Scanning the genome for gene single nucleotide polymorphisms involved in adaptive population differentiation in white spruce

Abstract: Conifers are characterized by a large genome size and a rapid decay of linkage disequilibrium, most often within gene limits. Genome scans based on noncoding markers are less likely to detect molecular adaptation linked to genes in these species. In this study, we assessed the effectiveness of a genome-wide single nucleotide polymorphism (SNP) scan focused on expressed genes in detecting local adaptation in a conifer species. Samples were collected from six natural populations of white spruce (Picea glauca) mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
241
5
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(265 citation statements)
references
References 98 publications
(202 reference statements)
17
241
5
2
Order By: Relevance
“…Although overall structure is relatively weak in many forest trees (for example, Namroud et al, 2008), differentiation of populations from range-wide collections tends to be stronger than that of more local collections (Ingvarsson, 2005;Keller et al, 2010;Slavov et al, 2012;Cushman et al, 2014;Evans et al, 2014;Zhou et al, 2014). For instance, Heuertz et al (2006) found that across large geographic distances, Picea abies is strongly differentiated across large geographic barriers, with F ST estimates approaching those that we found among genetic groupings.…”
Section: Population Structurementioning
confidence: 65%
See 1 more Smart Citation
“…Although overall structure is relatively weak in many forest trees (for example, Namroud et al, 2008), differentiation of populations from range-wide collections tends to be stronger than that of more local collections (Ingvarsson, 2005;Keller et al, 2010;Slavov et al, 2012;Cushman et al, 2014;Evans et al, 2014;Zhou et al, 2014). For instance, Heuertz et al (2006) found that across large geographic distances, Picea abies is strongly differentiated across large geographic barriers, with F ST estimates approaching those that we found among genetic groupings.…”
Section: Population Structurementioning
confidence: 65%
“…P. angustifolia is dioecious with putatively long-distance dispersal of pollen and seed, traits that are expected to minimize population structure (Hamrick and Godt, 1996), as has been shown in other species (for example, Namroud et al, 2008). Three factors could explain this result.…”
Section: Population Structurementioning
confidence: 83%
“…Weak population structure in white spruce from Québec has been reported in several studies using neutral genetic markers (Jaramillo-Correa et al, 2001;Namroud et al, 2008Namroud et al, , 2010 and was expected based on our previous analysis of a subset of the present discovery population . As a cautionary measure, we used the multidimensional scaling coefficients as population covariates for the GS analyses to control for any potential bias in prediction accuracy that could be brought about by such a population structure.…”
Section: Population Structurementioning
confidence: 96%
“…A population structure analysis was used to assess whether there were differences in allele frequencies among unobserved ancestral populations that could bias prediction accuracy estimates. Given the results obtained in previous studies conducted in the same area (JaramilloCorrea et al, 2001;Namroud et al, 2008Namroud et al, , 2010Beaulieu et al, 2011), we were expecting a weak or no population differentiation from SNPs. We used all available SNPs (m ¼ 6385) in multidimensional scaling and principal component analysis (Price et al, 2006) to estimate population covariates for each individual.…”
Section: Snp Genotypingmentioning
confidence: 99%
“…In contrast, genelinked microsatellites are located close to a gene (often in the untranslated regions) and are typically derived from an EST (expressed sequence tag) library (Bouck and Vision 2007). In genome scans, gene-linked markers represent a very useful means to assign functional genes possibly responsible for the eVect seen at an outlier locus (Vasemagi et al 2005;Namroud et al 2008).…”
Section: Introductionmentioning
confidence: 99%